2014
DOI: 10.1016/j.molstruc.2014.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Glass transition dynamics of anti-inflammatory ketoprofen studied by Raman scattering and terahertz time-domain spectroscopy

Abstract: A liquid-glass transition and a crystalline state of pharmaceutical racemic ketoprofen were studied by Raman scattering and the broadband terahertz time-domain spectroscopy (THz-TDS) in the frequency range from 9 to 260 cm-1. The low-frequency Raman scattering spectra clearly shows the remarkable change related to a liquid-glass transition at about T g = 267 K. After melt-quenching at liquid nitrogen temperature, a boson peak appears at about 16.5 cm-1 near and below T g and the intensity of quasi-elastic scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…The present result is consistent with a simulation study [33] and the experimental study of glassy sorbitol [38]. The experimental data and literature values of the boson peak frequency and shear modulus of several hydrogen bonded organic glass-forming materials including IMC are presented in Table 2 [39][40][41][42]. Different from the case of glycerol [40], which is a typical hydrogen bonded molecular glass former, the boson peak appears at a lower frequency in the IMC.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The present result is consistent with a simulation study [33] and the experimental study of glassy sorbitol [38]. The experimental data and literature values of the boson peak frequency and shear modulus of several hydrogen bonded organic glass-forming materials including IMC are presented in Table 2 [39][40][41][42]. Different from the case of glycerol [40], which is a typical hydrogen bonded molecular glass former, the boson peak appears at a lower frequency in the IMC.…”
Section: Resultssupporting
confidence: 89%
“…Comparison of boson peak frequencies of Raman scattering and shear modulus in hydrogen bonded organic glass-forming materials, glycerol, ketoprofen and indomethacin[39][40][41][42].…”
mentioning
confidence: 99%
“…By using the reflected or transmitted THz pulse from a sample, the dielectric property can observe directly without any assumption or Kramers-Kronig analysis [8,[9][10][11]. Permitivity in the terahertz region, especially, in far-IR, is dominantly determined by the ionic polarization which is derived from the optical phonons.…”
Section: Introductionmentioning
confidence: 99%
“…Peaks are described by spectral functions of dumped harmonic oscillators (DHO) to determine the mode frequency and damping of each mode. From these results and the reported results of DFT calculation and vibrational assignment [14], it is suggested that one possible origin of intense low-frequency peaks such as 1.38, 2.04 and 2.91 THz in a Raman scattering spectrum is the vibrations relate to hydrogen bonded ketoprofen dimers in the crystal structure [15].…”
Section: Crystalline Racemic Ketoprofenmentioning
confidence: 67%